Cytologický a embryologický atlas - Vaňhara, Petr; Dumková, Jana (Masaryk University Press, 2020)
Title in English: Atlas of Cytology and Embryology. This Atlas is intended for students of Faculty of Medicine and Faculty of Science of Masaryk University as a complementary study material in practical courses of histology and embryology, cytology, microscopic anatomy and others. It contains unique electron-microscopic images obtained at the Department of Histology and Embryology from mid of the 20th century to present. Schemes and microphotographs then show the most significant events in human development, histogenesis and organogenesis. We believe that this Atlas will obviate the ultrastructure of human body as well as the complexity of its development.